Against Plagiarism - Zhang, Yuehong (Helen). author. aut Link
XXIII, 162 p.
Keywords: This is the first volume of a book series dedicated to "Qualitative and Quantitative Analysis of Scientific and Scholarly Communication". Fighting plagiarism is a the top priority for STM publishing. A practical guide will importantly contribute to the awareness of the relevant communities, bringing to the surface the basic rules and examples from the literature.